EALÁT - Reindeer Herders Vulnerability Network Study - International Centre of Reindeer Husbandry, - (2009)
EALÁT is a Reindeer Herders Vulnerability Network Study and is a project that examines reindeer pastoralism in the light of climate change. On this site you will find background information about the project, presentations by Ealát researchers, details of the various work packages, lots of news related to the project, a wide variety of photo galleries, web video pages and more. Ealát is Sámi word with a multi layered meaning. Ealát signifies 'Pasture', but related words Eallu means 'Herd' while Eallin means 'Life' in the Sámi language. The primary research institution in EALÁT is the Sámi University College-Nordic Sámi Institute (SUC-NSI). A wide number of other research institutions are involved in the project, along with the Association of World Reindeer Herders(WRH) and the International Centre for Reindeer Husbandry. All these bodies are located in the heart of the Sámi region, Guovdageaidnu-Kautokeino, Norway.